Lipase‐mediated multicomponent synthesis of 1H‐Pyrazolo[1, 2‐b]phthalazine‐5, 10‐dione derivatives in a binary solvent medium. (28th October 2021) - Dalal, Kiran S.; Tayade, Yogesh A.; Wagh, Yogesh B.; Dalal, Dipak S.; Chaudhari, Bhushan L.
Abstract: A new method for the synthesis of 1 H ‐pyrazolo[1, 2‐ b ]phthalazine‐5, 10‐dione derivatives via lipase from the Aspergillus niger –catalyzed multicomponent reaction of aldehydes, malononitrile, and phthalhydrazide is reported herein for the first time. This novel method holds several advantages, including its efficiency, environmental friendliness, simple workup procedure, and good yield (70–86%). The effects of temperature, organic solvents, and water content were investigated. This protocol has the potential to replace traditional chemical synthesis routes for the synthesis of nitrogen‐containing heterocyclic compounds. Abstract : Lipase mediated synthesis of 1H‐pyrazolo[1, 2‐b]phthalazine‐5, 10‐dione derivatives